Kehalalan Menikahi Wanita Kitabiyyah: Telaah Konsep Naskh Mansukh dan Mubah Menurut Kitab al-Mahshul fi ‘Ilm Ushul al-Fiqh) - Muhammad Rizqi Romdhon (Matan : Journal of Islam and Muslim Society, 2022)
Marriage is a dream for men and women who do not have a partner. But the couples even found a partner of a different religion. For this reason, the authors feel the need to compile a study related to this. The preparation of this research is related to the concept of permissible or permissible which was formulated by Imam al-Rāzī in his book al-Mahshūl fi 'Ilm Ushūl al-Fiqh. The research objective of this paper is to find out more deeply about the lawfulness of marrying kitābiyyah women through the concept of permissible which is explained by Imam al-Rāzī in his book al-Mahshūl fi 'Ilm Ushūl al-Fiqh. The research method uses qualitative research, is content analysis, and is carried out through library research. Based on the research, with the permissible concept put forward by Imam al-Rāzī marrying a kitābiyyah woman is a permissible act which has been confirmed by the Qur'an and can bring good in it. But because this is a law that is permissible, then we can choose to do it or not to do it.